2015
DOI: 10.1186/s12886-015-0089-9
|View full text |Cite
|
Sign up to set email alerts
|

Binocular function to increase visual outcome in patients implanted with a diffractive trifocal intraocular lens

Abstract: BackgroundTo evaluate binocular visual outcome for near, intermediate and distance compared to monocular visual outcome at the same distances in patients implanted with a diffractive trifocal intraocular lens (IOL).MethodsThe study comprised of 100 eyes of 50 patients that underwent bilateral refractive lens exchange or cataract surgery with implantation of a multifocal diffractive IOL (AT LISA tri 839MP, Carl Zeiss Meditech, Germany). A complete ophthalmological examination was performed preoperatively and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 21 publications
6
27
0
6
Order By: Relevance
“…This finding was consistent with the results of other studies performed with trifocal IOLs [22, 27]. It seems that steep meridian incision may not have clinically relevant flattening effects and small incision size may account for this outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was consistent with the results of other studies performed with trifocal IOLs [22, 27]. It seems that steep meridian incision may not have clinically relevant flattening effects and small incision size may account for this outcome.…”
Section: Discussionsupporting
confidence: 92%
“…In the patients (54 eyes of 27 patients) who underwent AT LISA trifocal IOL implantation following phacoemulsification, Kohnen et al [26] reported good distance, intermediate and near VAs (0.10 logMAR or better), a high patient satisfaction, and a high spectacle independence at the postoperative 3rd month. Kretz et al [27] reported significant improvements in UDVA, UIVA, UNVA, and CDVA and better binocular outcomes as compared with monocular outcomes in 100 eyes of 50 patients who underwent AT LISA IOL implantation following cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Binocular uncorrected distance visual acuity was similar or slightly worse in our study than reported for the AT LISA Tri, although a higher percentage of patients achieved an uncorrected binocular visual acuity better than 0.1 [4, 7, 19]. Binocular uncorrected distance visual acuity was also slightly better with the Finevision [5, 6, 15].…”
Section: Discussionsupporting
confidence: 79%
“…This is important as individuals seeking spectacle independence want information on their expected functional capacity within the near range and this study provides new empirical evidence that can help inform expected visual outcomes for recipients of ERV IOLs. This study also assessed binocular visual acuity, which is an important outcome to include because of binocular summation and because it better equates to the circumstances in which a person usually functions . This study's use of micro‐monovision for ERV IOLs recipients makes binocular testing even more relevant for comparing visual acuity outcomes between ERV IOL and monofocal IOL groups.…”
Section: Discussionmentioning
confidence: 99%